Facebook and students’ attitudes toward writing - Wan Ahmad, Wan Rusli; Ahmed Mohamed, Ismaiel Hassanein; Mohd Ghalib, Mohd Feham; Mohammed Rawash, Fouad Mahmoud (2012)
The study aims at examining students' attitude towards Arabic Writing, prior and subsequent to the utilisation of Facebook, a social website, as a medium of writing activities and instructions. 21 students of Advanced Arabic Writing Skills at IIUM were selected as the subjects of the study. A 14-item questionnaire was distributed to the subjects prior and subsequent to the use of Facebook as a medium for writing activities. The questionnaire subsequent to the utilisation, which was distributed two months after, however, consisted of an extra item. Findings reveal that students demonstrated visible improvement of attitude towards Arabic writing then. The results thus, can be depicted that students attitude towards writing could be amplified by utilising social webs such as Facebook for the reason that writing itself is social in nature.